Aedes (Ochlerotatus) dorsalis - Khalin, A. V.; Aibulatov, S. V. (Zenodo, 2021)
Aedes ( Ochlerotatus ) dorsalis (Meigen, 1830) Northernmost records (Fig. 3a). 66°33 ′ 10.04 ″ N, 33°6 ′ 10.96 ″ E, RK, Loukhi Distr., White Sea Biological Station of Moscow State University (Tamarina & Aleksandrova, 1974); 64°32 ′ 23.68 ″ N, 40°30 ′ 56.71 ″ E, AP, Arkhangelsk (Sharkov, 1982); 67°16 ′ 56.7 ″ N, 63°39 ′ 9.26 ″ E, Komi, Vorkuta Distr., Khanovey (Panyukova & Ostroushko, 2017). Distribution . NWR: AP, Komi, LP, NP, PP, RK, SPb, VP. Adjacent countries: Norway, Sweden, Finland, Estonia, Latvia, Lithuania and Belarus. Europe (ranging northward to the UK, Belgium, the Netherlands and Denmark); the Holarctic. Published as part of Khalin, A. V. & Aibulatov, S. V., 2021, Northernmost records of mosquito species (Diptera: Culicidae) in northwestern Russia, pp. 46-63 in Zoosystematica Rossica (Zoosyst. Rossica) (Zoosyst. Rossica) 30 (1) on page 53, DOI:10.31610/zsr/2021.30.1.46, http://zenodo.org/record/10124237